Aplicación web para la gestión de compras y ventas para la empresa de ropa “Stephany’s Kids” en la ciudad de Atuntaqui - Aguirre Males, Jhon Freddy (2023)
Currently, textile companies face a highly competitive and dynamic business environment. Efficient management of purchasing and sales operations has become a critical challenge for their survival and growth. To address these challenges, companies turn to web applications as indispensable tools to streamline and optimize their operational processes. The management of purchases and sales constitutes the core of the supply chain and business activity in the textile industry. Acquiring quality raw materials, accurately tracking inventory, and effectively selling products are essential to maintaining a competitive position. However, managing these processes can be complex due to the variety of products, seasonal collections, and market demand fluctuations. In response to these challenges, specialized web applications for purchasing and sales management have emerged in clothing companies. These tools have become valuable allies by providing significant advantages. They offer greater visibility and control over inventory, allowing companies to minimize the risks of product loss and ensure sufficient stock to meet demand. Additionally, they facilitate supplier management and strategic purchasing by providing real-time access to data on product availability and prices. This thesis will explore relevant trends and tools in the development of web applications for purchasing and sales management in textile companies. Case studies will be analyzed, and best practices will be reviewed to enhance operational efficiency in the company. In summary, web applications for purchasing and sales management represent a valuable response to current challenges in the textile industry. These tools provide an integrated and efficient approach to addressing critical processes, enabling companies to stay agile and competitive in an ever-evolving marketKey words: management, purchases, sales, web application, inventory.